Pengaruh Komunikasi, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada SD Strada Dipamarga - Antonius Agung Febianto Hardiawan; Hendy Tannady (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study was to determine whether the variables of communication, work discipline and work environment have an influence on the performance of the employees of SD Strada Dipamarga. In this study, the data processing uses validity test, reliability test, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiples regression test, coefficient of determination, F test and T test with the help of SPSS 20.0. In the sample used as many as 40 respondents. In this study using a quantitative approach with purposive sampling technique method. Data collection was carried out by distributing questionnaires using a Likert scale to measure each statement. The results of the study stated that communication did not provide a significant effect on employee performance and for work discipline and work environment had a significant effect on employee performance.